1998
DOI: 10.1021/jo980467g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Synthetic Utilization of α-Functionalized Vinylphosphonates Bearing β-Oxy or β-Thio Substituents

Abstract: The beta-hetero-substituted vinylphosphonates 1a-c on treatment with LDA or LTMP were readily lithiated at the alpha-position of the phosphono group, and the resulting alpha-lithiovinylphosphonates were trapped with various electrophiles to afford the corresponding alpha-functionalized vinylphosphonates 2-14 in 55-96% yields. The Friedel-Crafts reaction of alpha-(silyl)- or alpha-(germyl)phosphonoketene dithioacetals 2, 9, or 4 with acid chlorides gave alpha-acylated phosphonoketene dithioacetals 15-19 in 53-9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 16 publications
0
40
0
Order By: Relevance
“…In almost all cases, working at 140°C allows to reduce noticeably the reaction time to few hours (3-6 h). Interestingly heteroaryl halides ( Table 2, entries 10-15), including 3-bromobenzothiophene (Table 2, entries [22][23][24], gave high yields showing the general applicability of the conditions.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In almost all cases, working at 140°C allows to reduce noticeably the reaction time to few hours (3-6 h). Interestingly heteroaryl halides ( Table 2, entries 10-15), including 3-bromobenzothiophene (Table 2, entries [22][23][24], gave high yields showing the general applicability of the conditions.…”
Section: Resultsmentioning
confidence: 95%
“…Furthermore, the reagents are not always readily accessible. As alternatives a-lithiation of boxy or b-thio vinylphosphonates [22], NaH catalysed olefination of benzenesulfinylmethylphosphonates [23] and addition of sodium organyl chalcogenolates to 1-alkynylphosphonates were reported [24]. However, in practice these methods led to formation of regioand stereo-isomers mixture.…”
Section: Introductionmentioning
confidence: 97%
“…57 Thus, a-sil- comparative study between silylated 36 and unsilylated 35 phosphonoketenes dithioacetals has demonstrated that the a-trimethylsilyl substituent was essential to increase reaction rate and yields. 57…”
Section: Scheme 13mentioning
confidence: 99%
“…Vinylphosphonates have been widely used as synthetic intermediates in organic chemistry [1] and investigated as biologically active compounds [2], especially in stereoselective synthesis of trisubstituted olefins [3] and heterocycle compounds [4]. Up to now, the synthesis of vinylphosphonates has been explored extensively.…”
Section: Introductionmentioning
confidence: 99%